IMPROVING STUDENTS’ VOCABULARY MASTERY USING SONG AND GAME IN ELEMENTARY SCHOOL - Yoga Naodin; Yana Yana (IKIP Siliwangi, 2022)
The purpose of this study is to describe the learning outcomes of the second-grade students in one of elementary school in lembang using songs and games as a media. This research used classroom action research (CAR). The characteristics of the action are described as repetitive actions to improve the teaching and learning process in the classroom research. Learning English aims to learn oral and written communication, the most important elements of language are vocabulary, pronunciation, grammar, and communication. Therefore, an educator must always remember the importance of creating a comfortable atmosphere, as well as arousing interest and motivation in learning English so that when students learn English from the start they learn in a pleasant atmosphere. Likewise, with the results obtained in this study using song and game media, researchers saw that several changes occurred in the behavior and the ability of students to become enthusiastic to be active in the learning outcomes increased in cycle 1 researching an average value of 65,83 in the medium category and the average value in the second cycle increased to 93,5 in the high category. Keywords: Song and Game, CAR, Vocabulary